Analysis of Physical Activity in Atoni Meto Traditional Sports on North Central Timor Regency - Talan, Rudobertus; Nay, Florianus Aloysius; Andiwatir, Alexius (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2022)
The purpose of the study was to determine the physical activity and traditional sports of Atoni Meto in North Central Timor Regency. The initial stage of the research method is that researchers develop research instruments that will be used to explore information from sources in depth through direct observation (observation), in-depth interviews, focus grup discussion, and documentation studies to find physical activities and traditional sports Atoni Meto